2.5x-(-8.2)=26.7

Simple and best practice solution for 2.5x-(-8.2)=26.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.5x-(-8.2)=26.7 equation:


Simplifying
2.5x + -1(-8.2) = 26.7

Multiply -1 * -8.2
2.5x + 8.2 = 26.7

Reorder the terms:
8.2 + 2.5x = 26.7

Solving
8.2 + 2.5x = 26.7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8.2' to each side of the equation.
8.2 + -8.2 + 2.5x = 26.7 + -8.2

Combine like terms: 8.2 + -8.2 = 0.0
0.0 + 2.5x = 26.7 + -8.2
2.5x = 26.7 + -8.2

Combine like terms: 26.7 + -8.2 = 18.5
2.5x = 18.5

Divide each side by '2.5'.
x = 7.4

Simplifying
x = 7.4

See similar equations:

| -8n+4(1+5)=6n-14 | | -11(x+9)=99 | | 6x^4*3x^4= | | y=-0.80(55)+136 | | 4.3*p=28.81 | | 5n-9=71 | | 5(x+4)=75 | | 6y-7=10y+25 | | y=-0.80(45)+136 | | 7(1y+-2)+8=3(1y+-4)+-2 | | y=-0.80(35)+136 | | -18-6k=6(13k) | | 2x-1=-x+5 | | 15x^3-7x-2= | | x+29=83 | | 16/7=m/21 | | 3x+5=-6 | | 0.2x-1.5=0.1 | | 3a^2+4=0 | | 16-5(3t-4)=8-(-2t+11) | | -7(-5x+7)=-49 | | 4m-4=9m | | 29=17-2x | | 3y+5=y | | 6(-6x-10)=-132 | | 3(x+1)+7(x+1)-6= | | 8x=8x+6 | | 0.5(x+4)-(10x+9)=-77 | | -4(1x+10)=-32 | | 25+15=x | | .33(3x+6)=8x+10 | | -6=-5x+6 |

Equations solver categories